PENGARUH GOOD UNIVERSITY GOVERNANCE DAN SISTEM PENGENDALIAN INTERNAL TERHADAP KINERJA PERGURUAN TINGGI MUHAMMADIYAH DI INDONESIA - Eka Aprilia; Rindu Rika Gamayuni; Saring Suhendro (Universitas Multimedia Nusantara, 2022)
Abstract— This study focuses on the effect of good university governance and internal control systems on higher education performance. This research is a quantitative research using path analysis. The population in this study were all Muhammadiyah higher education in Indonesia. And as for the research sample, the entire population consists of 154 universities throughout Indonesia. The results of this study are good university governance has a positive and significant influence on the performance of Muhammadiyah higher education, while the internal control system has a positive but not significant effect on the performance of Muhammadiyah higher education. This research is expected to provide benefits for Muhammadiyah universities and other universities in improving performance related to good university governance and internal control systems. In the development of science, especially the discussion on the performance of higher education institutions, the results of this study are expected to be a reference for future research related to good university governance and internal control systems and to contribute to conducting research at Muhammadiyah universities with indicators of 9 criteria accreditation that has not been carried out in previous research which can further provide an overview of the performance of Muhammadiyah higher education in Indonesia. Keywords: Good University Governace; Internal Control; Higher Education Performance